A “Mesolithic Living” Project - Rüdiger Kelm (EXARC Journal)
From the 27 July to the 6 September 2015 the Stone Age Park Dithmarschen (Archaeological-Ecological Centre Albersdorf, AÖZA) organised a Mesolithic living history experiment in its newly constructed ‘Mesolithic Settlement’ finished last year. The experiment sought to investigate, through careful reconstruction, how people may have carried out their daily lives in the Mesolithic period. All activities and reconstructed material were scientifically documented under the supervision of Dr Linda Hurcombe by archaeologists from Exeter University in Southwest England (an OpenArch project member). The scientific results will be published by Exeter University while its detailed documentation will be published by the Stone Age Park, both in the form of a magazine and a brochure.